Sharia-Based Diversification Strategies for Rubber Farmers in Facing Price Fluctuations - Hadijah Indah Sari; Inayatul Maula (Universitas Islam Internasional Darullughah Wadda'wah, 2026)
The persistent fluctuation of global natural rubber prices and associated non-market risks continue to challenge the sustainability and income stability of rubber farmers, particularly in Desa Salam Babaris, Tapin Regency. This economic uncertainty compels farmers to adopt adaptive strategies rooted not only in material profit but also in principles of ethics and justice. This study aims to analyze the diversification and adaptation strategies employed by rubber farmers in response to price shocks, specifically from the perspective of Sharia Economic principles. The research utilizes a qualitative approach with a case study method, gathering data through in-depth interviews, and employing an optimization analysis framework based on Sharia diversification theory. The findings indicate that farmers effectively employ crop diversification (such as rice and vegetables) as an income buffer and utilize direct marketing for cost efficiency. These strategies are strongly supported by robust Social Capital within Farmers Groups (Poktan), which serves as a mechanism for ta'awun (mutual help) and proactive agronomic adaptation against environmental risks. These practices enhance the farmers' economic resilience and are substantially aligned with the principles of justice ('adl) and honesty (shiddiq). We conclude that this integrated adaptation model is effective in achieving sustainable economic well-being and contributes a valuable reference for developing just, sustainable, and ethics-based agricultural policies.